Fanatisme Beragama Yes, Ekstrimisme Beragama No; Upaya Meneguhkan Harmoni Beragama Dalam Perspektif Kristen - Rohmatika, Ratu Vina; Hakiki, Kiki Muhamad (AL-ADYAN, 2018)
The articlefocuses on how the Christian presents a teaching doctrine of difference. Based on the research results, although Christian doctrine contains the exclusive doctrines, it isfound in its scripturesthe inclusive (humanist) doctrines. Christianity teaches that fanatics to human values as substantial religious values.This situation strengthens that every religion, including Islam, Buddhism, Hinduism, has inclusive teaching of difference. Being religious fanaticism is important, but behaving extremists is not necessarily, especially those who are different. There are many ways that can be done to cultivate the attitude form of religious harmony such as disseminating pluralism, organizing interfaith dialogue, and studying religious studies.